Latent semantic analysis of service quality in the Airline Industry: A consumer perspective - Muhammad Muazzem, Hossain; Ouedraogo, Noufou; Rezaniac, Davar (Universiti Malaysia Perlis (UniMAP), 2011)
The 2nd International Conference on the Roles of Humanities and Social Science in Engineering (ICoHSE 2010) organized by Universiti Malaysia Perlis (UniMAP), 12th - 14th November 2010 at Bayview Beach Resort, Penang, Malaysia.